ANTIBACTERIAL ACTIVITY OF LIQUID CRYSTAL NANOPARTICLES GEL OF BINJAI LEAVES METHANOL EXTRACT (MANGIFERA CAESIA JACK. EX. WALL.) AGAINST PROPIONIBACTERIUM ACNES - RAMADHAN, HAFIZ; FORESTRYANA, DYERA; JAMALUDIN, WAHYUDIN BIN; PALGUNO, SATRIYO KRISNA (International Journal of Applied Pharmaceutics, 2022)
Objective: This study aims to compare the anti-Propionibacterium acnes activity between the optimum formula of gel liquid crystal nanoparticles of Binjai leaves methanol extract and the gel of extract without the liquid crystal nanoparticles system. Methods: Preparation of liquid crystal nanoparticles using top-down methods with 6% Capmul-GMO 90 and 5% Plantacare 818. Preparation of the optimum gel formula using 7% Viscolam Mac 10 as a gelling agent. The antibacterial activity was evaluated by cup plate technique and clindamycin was used as a positive control. Results: The results obtained are liquid crystal nanoparticles based gel of methanol extract of Binjai leaves produces a strong category as anti-Propionibacterium acnes with an average inhibition of 15.33±1.2413 mm and the gel of extract without the liquid crystal nanoparticles system only produces 13.53±1.241 mm. Conclusion: The gel of Binjai leaves extract with a liquid crystal nanoparticles system has a higher antibacterial effect on Propionibacterium acnes than the gel of extract without the liquid crystal nanoparticles system.